2018
DOI: 10.5505/tjtes.2018.29434
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting the early mortality of trauma patients

Abstract: BACKGROUND:The aim of this study was to identify factors predicting early mortality in trauma patients. METHODS:This was a study of 6288 trauma patients admitted to the hospital between July 2011 and June 2016. Among the variables recorded for a prospective trauma registry, the following were selected for analysis: sex; age; a combination of the Glasgow Coma Scale score, age, and systolic blood pressure (SBP) (GAP); a combination of the mechanism of injury, the Glasgow Coma Scale score, age, and SBP (MGAP); SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…On the contrary, A prospective study [15] showed that SpO 2 was a better parameter than RR and could add significant value to other variables in predicting mortality in trauma patients. Otherwise, A recent study revealed pragmatic value of SpO 2 in trauma and indicated that SPO 2 can effectively predict the 24-hour mortality of trauma patients [1].…”
Section: Plos Onementioning
confidence: 99%
See 4 more Smart Citations
“…On the contrary, A prospective study [15] showed that SpO 2 was a better parameter than RR and could add significant value to other variables in predicting mortality in trauma patients. Otherwise, A recent study revealed pragmatic value of SpO 2 in trauma and indicated that SPO 2 can effectively predict the 24-hour mortality of trauma patients [1].…”
Section: Plos Onementioning
confidence: 99%
“…The vast majority of the previous studies on the prediction of early in trauma patients are based on the mortality in-hospital or 28 days [3,6,9,19,21,22], not early mortality in the emergency room. A recent study [1] Identified variables that can be quickly measured to predict 24-hour early mortality, showing that SPO2 < 90% can be used to predict early mortality. However, it did not address the correlation between SI and early mortality in trauma patients.…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations